2007
DOI: 10.1097/brs.0b013e31811329ac
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity in Chronic Disabling Occupational Spinal Disorders Has Minimal Impact on Functional Restoration Socioeconomic Outcomes

Abstract: Despite intensive management of psychiatric disorders during interdisciplinary functional restoration for CDOSD, several disorders were found to be associated with less successful outcomes. Poorer work outcomes were more common with specific (and comorbid) Axis I psychiatric disorders. Opioid dependence was the single disorder associated most often with less successful outcomes. Despite these findings, the large majority of patients demonstrated successful outcomes. Depression did not independently link to les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
1
17
0
2
Order By: Relevance
“…The presence of a psychiatric disorder slowed down the perception of analgesic effects and impaired the outcome of ziconotide. This is in agreement with the literature, where it has been shown that the presence of a psychiatric disorder (in particular the panic) is associated with a lack of success in the treatment of pain (31) and that optimizing the use of antidepressants results in a better outcome for pain treatment (32). Notably, 66% of our sample showed at least one psychiatric disorder.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of a psychiatric disorder slowed down the perception of analgesic effects and impaired the outcome of ziconotide. This is in agreement with the literature, where it has been shown that the presence of a psychiatric disorder (in particular the panic) is associated with a lack of success in the treatment of pain (31) and that optimizing the use of antidepressants results in a better outcome for pain treatment (32). Notably, 66% of our sample showed at least one psychiatric disorder.…”
Section: Discussionsupporting
confidence: 93%
“…There can be individual complications during rehabilitation, and in rehabilitation programs, after injury. A diagnosis of an Axis II disorder has previously been identified as predictive of noncompletion [53,54], poor outcome [55] and non-adherence [56] in treatment programs. Daily skin care and treatment over a long period of time after a burn can be demanding, and conceivable difficulties could result in worse actual as well as perceived skin health.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous studies showing high rates of dropout from different rehabilitation programs. [22][23][24][25] …”
Section: Discussionmentioning
confidence: 99%